(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
69 species of the lichens and 14 species of the lichenicolous fungi on the granite outcrops of Bobrynets ravine (town Bobrynets, Kirovograd region) in northern steppe of Ukraine were found. Among them Didymocyrtis ramalinae (Roberge ex Desm.) Ertz, Diederich & Hafellner, Pyrenopsis subareolata Nyl., Thallinocarpon nigritellum (Lettau) P.M. Jørg. are new species for plain part of Ukraine. 54 species are new for Kirovograd region. The annotated lists of the species are provided. This territory is proposed as protected area with status of the regional landscape reserve «Bobrynetska balka».